Is tDCS an Adjunct Ergogenic Resource for Improving Muscular Strength and Endurance Performance? A Systematic Review - Machado, Sergio; Jansen, Petra; Almeida, Victor; Veldema, Jitka (Frontiers in Psychology, 2019)
Exercise performance is influenced by many physical factors, such as muscle strength and endurance. Particularly in the physical fitness and sports performance contexts, there are many types of ergogenic aids to improve muscular strength and endurance performance, with non-athletes and even athletes using illegal drugs to reach the top. Thus, the development of innovative methods to aid in exercise performance is of great interest. One such method is transcranial direct current stimulation (tDCS). A systematic search was performed on the following databases, until January 2019; PubMed/MEDLINE, SCOPUS, and Pedro database. Studies on tDCS for muscular strength and endurance performance improvement in non-athletes and athletes adults were included. We compared the effect of anodal-tDCS (a-tDCS) to a sham/control condition on the outcomes muscular strength and endurance performance. We found 26 controlled trials. No trial mentions negative side effects of the intervention. The data show differences between the studies investigating muscle strength and the studies evaluating endurance, with regard to successful use of tDCS. Studies investigating the efficiency of tDCS on improving muscular strength demonstrate positive effects of a-tDCS in 66.7% of parameters tested. In contrast, in studies evaluating the effects of a-tDCS on improving endurance performance the a-tDCS revealed a significant improvement in only 50% of parameters assessed. The majority of the data shows consistently influence of a-tDCS on muscular strength, but not to endurance performance. The results of this systematic review suggest that a-tDCS can improve muscular strength, but not to endurance performance.